2021
DOI: 10.3390/genes12081258
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Identification of circRNAs in Alzheimer’s Disease

Kyle R. Cochran,
Kirtana Veeraraghavan,
Gautam Kundu
et al.

Abstract: Mammalian circRNAs are covalently closed circular RNAs often generated through backsplicing of precursor linear RNAs. Although their functions are largely unknown, they have been found to influence gene expression at different levels and in a wide range of biological processes. Here, we investigated if some circRNAs may be differentially abundant in Alzheimer’s Disease (AD). We identified and analyzed publicly available RNA-sequencing data from the frontal lobe, temporal cortex, hippocampus, and plasma samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Some studies reported that circRNAs could play an important role in AD [ 8 , 15 ], even as possible biomarkers [ 8 ]. However, to our knowledge, only one paper was published investigating a profile of plasmatic circRNAs in AD [ 16 ], while no studies are available on subjects with MCI. The study reported that 15 circRNAs were significantly higher in participants with AD compared to HCs from two different populations (GSE161199 and PRJNA574438).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that circRNAs could play an important role in AD [ 8 , 15 ], even as possible biomarkers [ 8 ]. However, to our knowledge, only one paper was published investigating a profile of plasmatic circRNAs in AD [ 16 ], while no studies are available on subjects with MCI. The study reported that 15 circRNAs were significantly higher in participants with AD compared to HCs from two different populations (GSE161199 and PRJNA574438).…”
Section: Discussionmentioning
confidence: 99%
“…It is helpful for the diagnosis and treatment of AD to understand how related molecules participate in these processes. Due to the rapid development of high-throughput RNA-seq technologies, the dynamic expression patterns and functions of circRNAs in AD have been characterized recently in a large number of studies ( Dube et al, 2019 ; Cervera-Carles et al, 2020 ; Cochran et al, 2021 ).…”
Section: Involvement Of Circrnas In Cognitive-related Diseasesmentioning
confidence: 99%
“…This autophagic protein is important for clearing amyloid peptides and is less abundant in the AD brain. Consequently, ciRS-7 may participate in AD pathogenesis [ 135 , 137 , 138 ].…”
Section: Circular Rnasmentioning
confidence: 99%